Knowledge, Attitudes, and Practices of Adults for Periodic Health Assessment in Al Ahsa, Saudi Arabia - Alhafedh, Fatimah Yousef; Almusaileem, Rawan Ahmed; Aljaafar, Zahraa Hassan; Alaayesh, Rayhanah Saleh; Estrella, Edric (UI Scholars Hub, 2025)
Background: Regular medical consultation, such as annually or semi-annually for check-ups, especially to diagnose chronic conditions, is essential for health maintenance, particularly in adults. The aim of this study is to analyze the knowledge, attitudes, and practices of adults aged 30 years or older for obtaining periodic professional health assessment in the city of Al Ahsa in Saudi Arabia. Methods: A cross-sectional study was conducted in a total sample of 472 adults. Multistage sampling was employed, and data were collected using a Google Forms survey and analyzed using JASP and OpenEpi. Descriptive and logistic regression analysis was used to analyze the data. Results: Of the participants, 46.2% reported engaging in regular medical consultation. While knowledge and positive attitudes were generally high, logistic regression showed that attitude was significantly associated with consultation behavior. Conclusion: A gap exists between knowledge/attitudes, and practice regarding regular medical consultation in Al Ahsa. Interventions targeting attitudes may be effective in promoting regular medical consultation.